PERANAN KARANG TARUNA DALAM MENUMBUHKAN KEPEDULIAN SOSIAL PEMUDA - Tia Oktaviani; Damanhuri Damanhuri; Wika Hardika Legiani (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2019)
This study aims to find out how the role of Youth Organization in fostering social awareness of youth, any form of social care carried out by Karang Taruna of Perumahan and supporting factors and inhibitors of Bukit Permai Youth Organization in fostering youth social awareness. Theory uses Social Concern theory According to Crandall in Addision E. Gradel (2009: 35) includes motivation, understanding, empathy and contribution. The research method uses qualitative descriptive. Research informants from the Bukit Permai Housing Youth Organization and Pimpina in the Bukit Permai Housing Community Area. Test the validity of the data using source triangulation and member check techniques. Data analysis used qualitative data analysis of Miles and Huberman. The results of the study regarding the role of youth organizations in fostering social awareness include (1) Karang Taruna members providing motivation to youth by inviting them to contribute to social activities for their development and the environment, (2) asking for proposals for ideas and ideas from non youth members, ( 3) providing an understanding of the implementation of social activities needed so that the community environment is conducive, (4) inviting youth to be involved in youth activities, especially planning social activities. Forms of social activities such as community service cleaning sanitation channels, cleaning public facilities, installing street lighting in each block, conducting fogging, donating activities to the poor and disaster, making hydroponic parks in collaboration with RTs, focus group discussions, youth discussion activities internal routine.